ETNOZOOLOGI SUKU DAYAK KANAYANT DI DESA BABANE KABUPATEN BENGKAYANG - Pilatus, .; Kartikawati, S M; Anwari, M Sofwan (Universitas Tanjungpura, 2017)
The knowledge gained from experience is very valuable and cannot be generated instantly. Dayak Kanayant in the village Babane having knowledge the use of fauna that are seen as has done based on the experience such as leveraging for to drug, ritual, mystical, consumption, artistic value, omen and others. This knowledge have to documented remember high activity of the opening of land by the community that will be influential in the population for that is in the area that it would deprive of community knowledge will the use of animals. The purpose of this research is to the knowledge of the animals that is occupied, pattern the use and parts of an organ that is occupied. Methods used is the survey to technique interview the respondents with snowball sampling. Respondents obtained as many 19 people. Obtained 47 kind of for of 43 members of the family who used by the Dayak of Kanayant, of 43 the family most of the every the family only consisted of 1 species, except for the family of columbidae, muscicapidae, ranidae and the trionychidae each found two species. The use of vary from of the use of consumption, treatment, ritual, mystical, omen, and artistic value. The use of most that is as consumption needs namely 52 %. Pattern the use of animals that is the use of directly and indirectly, direct use as an omen (mystical), the use of indirect such as leveraging for consumption, treatmen, artistic value and rituals. The parts of an animal that is occupied covering full body, meat, bile, the intestines, fat, bone, hearts, eggs, teeth, head, blood, sound, horns and shell. Meat is part much used many as 30 species.Keywords: Dayak Kanayant, ethnozoology, wildlife, utilization.